Diagnosis and management of late-onset postpartum preeclampsia at the first level of care. Case report. - Rivadeneira, Josue (2023)
Introduction: Late-onset postpartum hypertension occurs from 48 hours to 6 weeks postpartum, affecting 2% of pregnancies related or not to a history of gestational hypertension. Postpartum preeclampsia has an incidence of 5.7% at 72 hours postpartum and is associated with several maternal factors such as age (≥ 35 years), ethnicity (black) and obesity (BMI ≥ 30), presenting higher risk in multiple pregnancies, elderly mothers (older than 35 years) low-income households. The most frequent symptoms of this pathology are headache, dyspnea, visual disturbances and peripheral edema. Objective: To describe the experience in a primary care health center,  the management of a patient diagnosed with late-onset postpartum preeclampsia, as well as the clinical characteristics and risk factors. Case presentation: We present the case of a 32-year-old indigenous patient with a history of twin birth who in her puerperium control at 72 hours presented arterial hypertension, frontal headache, peripheral edema and proteinuria establishing the diagnosis of late-onset postpartum preeclampsia, after which treatment was initiated at the first level of care, making referral difficult due to cultural characteristics. Conclusions and recomendations: Late-onset postpartum hypertension is an infrequent pathology in the puerperium, underdiagnosed, with short and long-term cardiovascular complications, so its diagnosis, differentiation and management should be optimal based on existing recommendations.